Modelling and comparative performance analysis of tin based mixed halide perovskite solar cells with IGZO and CuO as charge transport layers. (25th May 2021) - Deepthi Jayan, K.; Sebastian, Varkey
Summary: n this study, SCAPS 1D software package is used for modelling tin based mixed halide perovskite solar cells (PSCs) with IGZO and CuO as electron transport material and hole transport material, respectively. Photovoltaic performance parameters of these PSCs are compared to that of pure lead based and lead‐free PSCs with the same charge transport layers. The study shows that the pure tin‐based PSCs are superior in performance to other device configurations. IGZO and CuO are found to be better substitutes for the commonly used unstable and expensive transport layers, TiO2 and SpiroMeOTAD. The study also shows that back metal contacts with work function above 5.5 eV provides stable performance parameters. The study includes an analysis of the influence of various input parameters of the perovskite absorber layer‐ thickness, dopant concentration, total defect density, band gap and electron affinity‐ on the photovoltaic performance parameters. PSCs with MASnI3 as absorber layer show the best performance with a fill factor (FF) and a power conversion efficiency (PCE) of 68.38% and 25.08%, respectively. The effect of internal resistances and temperature dependence are also analysed. For PSCs with single halide perovskites as absorber layer, even a low value of series resistance of 5 Ω cm 2 degrades the performance of the device and a large value of shunt resistance of 5000 Ω cm 2 enhances the performance parameters of the device. Abstract : In this study, the optimised solar cell configurations are obtained by modelling the solar cells with IGZO as the Electron Transport Material (ETM), CuO as the Hole Transport Material (HTM) and diverse back contact metals using either MAPbI3 or MASnI3‐X BrX (with X = 1, 2, 3) as absorber layers with the help of SCAPS 1D tool. All the device configurations exhibited good performance parameters with the lead free MASnI3 based PSC showing a highest PCE of 25.08%. The study indicates that the low‐cost metal oxide IGZO can act as a better substitute as ETM for the commonly used TiO2 layer and the less expensive and easy to fabricate inorganic metal oxide CuO as HTM can provide a high PCE for the analysed device configurations. The performance analysis shows that the low cost back contact metals like Pd, Pt, and Se can provide a stable performance for PSCs similar to the popular but expensive metal contact, Au.